2010 6th International Conference on Wireless and Mobile Communications 2010
DOI: 10.1109/icwmc.2010.63
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antenna Configurations for Wireless Broadband Vehicular Communications

Abstract: Abstract-In this paper, mobile WiMAX trials are analysed to investigate the vehicular down-link performance for a number of on-car antenna configurations. The directionality and optimum polarization of the vehicular antennas are shown to improve both the range and throughput of the system. These improvements are attributed to the additional directive gain, and the reduced multi-input multi-output spatial correlation that results from orthogonal polarization. The mobile-WiMAX trials cover an urban vehicular sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is stated in [5] that orthogonality of antenna polarisation is maintained for 50 m -200 m in adhoc networks. Authors in [6] concluded that orthogonally polarised directional devices achieve highest throughput in vehicular networks. Authors in [7] have observed that with directional antenna and polarisation diversity, maximum network throughput is obtained up to a communication distance of 800 m in outdoor environments.…”
Section: Related Workmentioning
confidence: 99%
“…It is stated in [5] that orthogonality of antenna polarisation is maintained for 50 m -200 m in adhoc networks. Authors in [6] concluded that orthogonally polarised directional devices achieve highest throughput in vehicular networks. Authors in [7] have observed that with directional antenna and polarisation diversity, maximum network throughput is obtained up to a communication distance of 800 m in outdoor environments.…”
Section: Related Workmentioning
confidence: 99%